STRUKTUR WACANA DAN DIKSI DALAM IKLAN BERITA DUKA DI MEDIA CETAK SURAT KABAR HARIAN KOMPAS - Takasihaeng, Erika Janet (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Problems There are two kinds of discourse, verbal and nonverbal, used in the daily activities. Verbal or interactive discourse is produced from communication process between speaker and hearer. The art of choosing a word that used in the discourse is based on the way of the writer. The words exist it the decease news of Kompas newspaper has informative discourse. Aim of the Research The aim of this research is to describe the discourse structure and the word choosing of decease news of Kompas newspaper has informative discourse. Method The writer used descriptive because the data were collected, analyzed and presented as they were. In the method application, technique is used to applied the method. Techniques used were population, sample, data providing method, data analysis technique, and data analysis  presentation.   Conclusion It can be concluded that the discourse structure in the decease news of the Kompas newspaper divided into three parts, they are; head of discourse, body of discourse, and closing. Head of discourse is functioned as introduction; body of discourse is functioned as information of the identity of the late person, time, and place of funeral; finally,  the closing part of the discourse informed the families that left. The writer also concluded that there were words choosing by the provider such as bapa and rahmatullah, belasungkawa, berpulang, dikremasi, dikebumikan, disemayamkan, telah, and jenazah. In the discourse of advertisement, decease news used euphemism to express the feeling instead of words that consider as rough in daily used. The words like mati replaced by meninggal dunia, of wafat that softer that previous one.   Keywords: discourse analysis, words, decease news, kompas